2019
DOI: 10.3389/fmats.2019.00152
|View full text |Cite
|
Sign up to set email alerts
|

Restricting Polyoxometalate Movement Within Metal-Organic Frameworks to Assess the Role of Residual Water in Catalytic Thioether Oxidation Using These Dynamic Composites

Abstract: Comprised of high valent metal centers connected via oxide bonds, polyoxometalates (POMs) have a rich history in redox reactions. These discrete metal oxide clusters often are immobilized on heterogeneous supports to increase stability and allow for recyclability for catalytic reactions. One such support is the metal-organic framework (MOF), NU-1000. When POMs are installed into NU-1000, they are first sited in the mesoporous channel. Upon application of heat and removal of some physisorbed water, the POMs mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 49 publications
(50 reference statements)
0
17
0
Order By: Relevance
“…The composite material PV 2 Mo 10 @NU-1000 was synthesized in a similar manner to that for PW 12 @NU-1000. ,, Briefly, NU-1000 was added to an aqueous solution of H 5 PV 2 Mo 10 O 40 and allowed to sit for 3 days. After, the solid was washed rigorously with water and ethanol before activation via supercritical CO 2 drying, yielding PV 2 Mo 10 @NU-1000-scCO 2 (Figure left; see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The composite material PV 2 Mo 10 @NU-1000 was synthesized in a similar manner to that for PW 12 @NU-1000. ,, Briefly, NU-1000 was added to an aqueous solution of H 5 PV 2 Mo 10 O 40 and allowed to sit for 3 days. After, the solid was washed rigorously with water and ethanol before activation via supercritical CO 2 drying, yielding PV 2 Mo 10 @NU-1000-scCO 2 (Figure left; see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the selectivity of the reaction is highly important. Two different POMs, H 3 PW 12 O 40 and H 5 PV 2 Mo 10 O 40 , have been encapsulated in NU-1000 (named as PW 12 @NU-1000 245,247,248 and PV 2 Mo 10 @NU1000, 244 respectively) for the oxidation of CEES using hydrogen peroxide (H 2 O 2 ) as the oxidant. Results showed that while 100% conversion of the parent agent is successfully done, the problem is the selectivity toward the desired non-toxic oxidation product.…”
Section: Heterogeneous Catalysismentioning
confidence: 99%
“…In this section, we will discuss how MOFs have been enlisted to support POMs and to provide reactant accessibility. [170][171][172][173][174][175] Steric encapsulation of POMs relies on size matching between the MOF cavity and POM, where the MOF pore is big enough to accommodate a POM, but the apertures/windows are small enough to prevent the POM from leaving. 176 To this end, Mukhopadhyay et al 177 prepared a composite by growing ZIF-8 around the pre-formed POM (Fig.…”
Section: Mof-linker-based Presentation and Isolation Of Catalystsmentioning
confidence: 99%
“…23). 170,172 Siting in the hexagonal mesopore can be considered a kinetically determined location, while the trigonal micropore is the thermodynamically favoured location. Interconnecting the meso-and micro-pores are smaller pores that can distort sufficiently to permit the observed POM migration.…”
Section: Mof-linker-based Presentation and Isolation Of Catalystsmentioning
confidence: 99%